Official report of the commandant of cadets of the battle at New Market, &c. &c. &c. - Richardson, William H. (William Harvie), 1795-1876 (Document (Virginia. General Assembly), 1865)
January 1865 official report from the Commandant of the Cadets of the Virginia Military Institute regarding the corps' participation in the Battle of New Market on June 27, 1864.